Contradiction between input and output of Chinese scientific research: a multidimensional analysis - Cao, Qinwei (Scientometrics, 2020)
Why does China rank first in the number of researchers and second in the total amount of R&D fund investment in the world, but lag behind other countries in the number of international patent applications and the market share of high-quality achievements? Prior researches have mostly answered this question based on a single perspective and dimension of qualitative judgment, the overall persuasion is not enough. For this reason, from the perspective of international comparison, we first use the standard data among countries in the OECD database to analyze external causes of the contradictions from macro level, innovation subject, research type and micro individual four dimensions to illustrate China’s international status and room for improvement. Then, we conduct a questionnaire survey to comprehensively analysis internal causes of the contradiction. We use a grounded theoretical approach to extract the core ideas to encode the answers to the unresolved questions at three levels. Finally, we put forward policy suggestions from the aspects of scientific research talents training, R&D fund utilization and assessment system respectively. We hope to further enrich the theoretical system of scientific and technological (S&T) innovation and provide relatively complete empirical evidence for the government, universities, enterprises and other relevant R&D subjects to make scientific decisions.